A study on the construction of a model for sustained ICS medication adherence behavior in children with asthma - Yan, Li; Guo, Rong; Wu, Liping; Yin, Chunlan; Tang, Jianlan (Frontiers in Public Health, 2025)
ObjectiveTo develop a Sustained Adherence Behavior Model for inhaled corticosteroids (ICS) Medication in Children with Asthma.MethodThrough literature review and semi-structured interviews, a questionnaire item pool was developed to assess the factors influencing the medication adherence behavior of asthma children using ICS. Expert consultation was conducted, involving two rounds of inquiries with experts, ultimately resulting in the development of the influence factors scale. The scale, along with the general situation survey of asthma children and the bronchial asthma medication adherence scale, was used to survey 370 asthma children who visited the outpatient department. Finally, a model of ICS medication adherence behavior for asthma children was established.ResultsThe positive coefficients of the two rounds of expert consultation were 90.5% and 95.2%, and the Kendall concordance coefficients were 0.384 and 0.278 (both P < 0.01). The Cronbach's α coefficient of the questionnaire was 0.925. The final asthma children's ICS medication adherence behavior influence factors scale consisted of 5 first-level items and 23 second-level items. Structural equation modeling analysis showed that the direct effects on medication adherence were behavioral intention (0.522), medication knowledge (0.193), and medication belief (0.181). The indirect effects were normative belief (0.161) and self-efficacy (0.140). The coefficient of determination (R2) for the influencing factors was 0.46 (P < 0.01).ConclusionThe behavioral model based on the Health Belief Theory effectively analyzes the factors influencing the ICS medication adherence behavior of asthma children, with the greatest impact coming from behavioral intention, followed by medication belief and medication knowledge.